The need and development for a value-added toolkit—A case study with Montana specialty fruit growers - Garg, Sumedha; Jha, Gaurav; Kim, Sun-Hwa; Miller, Zachariah; Kuo, Wan-Yuan (Frontiers in Sustainable Food Systems, 2023)
Cold-hardy small fruits and berries have the potential for specialty fruit growers in the Intermountain West, where the climate is not suited for conventional fruit crops. In the last seven years, approximately 50 varieties of cold-hardy, bush fruit types have been researched in western Montana. Hence with the increased small fruit and berry production, and interest of specialty fruit growers in value-added product development, this paper utilized participatory action research (PAR) to develop a value-added product development toolkit with specialty fruit growers and used an integrated logic model to discuss creating and implementing the toolkit. Firstly, we used an online survey to identify the needs and challenges of specialty fruit growers. Next, a value-added toolkit is drafted using the principles of design thinking and involving a student-grower partnership. Thirdly, the specialty fruit grower’s interest in and feedback on the drafted toolkit is evaluated using focus group discussions and individuals interviews, and the results are used to revise the toolkit. Lastly, the short, medium and long-term outcomes for this toolkit are discussed using the logic model. From the survey, 61% of specialty fruit growers indicated an interest in value-added opportunities. Yet, focus group discussions and individual interviews found the biggest barriers to value-added product development are cost, resources, and environment. This indicated a co-created toolkit will be a beneficial solution. During focus group and individual interviews, the growers suggested including the toolkit as part of coursework in semester-long classes. This will address issues of continuity and funding. Overall, this study deployed PAR methods to propose with Montana specialty fruit growers a solution to their increasing needs in value-added pursuits, implying short-term economic benefits but also long-term socio-ecological benefits. The participatory model of creating value-added resources presented by this paper can benefit other small-scale specialty crop growers in underserved regions.